Masyarakat Peduli Lingkungan Berbasis Pendidikan Agama Islam (Studi Kasus Komunitas Warga Kebun Buku Sekolah Alam Rimba Raya) - Nazopah, Nada (Jurnal el-Huda, 2025)
This study aims to describe the development of the youth's concern for the village environment that formed a forum called the Community of Residents of the Rimba Raya Nature School Book Garden (KWKB SARR) in running a series of programs to protect the surrounding environment—descriptive qualitative method with case study research design. Observation, interviews, and documentation were used to obtain data in this research. The results show that the Rimba Raya Natural School Book Garden Community makes a significant contribution to environmental preservation, especially in Mambalan Village with various programs such as the Islamic Education-Based Reading Garden program, the Family Economy-Based Islamic Education Ecology Program, and Islamic Education from/and for the Village. The successful implementation of these programs from the Islamic Religious Education (PAI) perspective is a development of the application of Islamic Religious Education values in moral material towards the environment.